PENYULUHAN MANFAAT RASIO KEUANGAN PADA SISWA/I YAYASAN PRIMA UNGGUL DI JAKARTA TIMUR - Indrajati Widjaja, MF Djeni (Jurnal Serina Abdimas, 2023)
Financial Ratios are a Company analysis tool for assessing a company's performance based on a comparison of financial data contained in financial statements (balance sheet/statement of financial position, report/income statement and statement of cash flows). Ratio is a measuring tool used by companies to analyze financial statements. Using an analytical tool in the form of financial ratios can explain and provide an overview of the good or bad condition or financial position of a company from one period to the next. The Prima Unggul Foundation, which houses package C high school students, has several small business activities that require accounting records. So far, students have recorded their finances in a simple and concise manner and sometimes lack operational funds. This PKM activity is carried out online with presentation of material and discussion of its implementation so that students become more aware of preparing financial reports and making financial ratio analysis that will describe the condition of their business ventures. Salah satu alat analisis Perusahaan untuk menilai kinerja berdasarkan perbandingan data keuangan yang terdapat pada laporan keuangan (neraca/laporan posisi keuangan, laporan/laba rugi dan laporan arus kas) adalah Rasio Keuangan. Analisis laporan keuangan seringkali menggunakan alat ukur berupa rasio yang dapat menjelaskan dan memberikan gambaran tentang baik atau buruknya keadaan atau posisi keuangan suatu perusahaan dari suatu periode ke periode berikutnya. Yayasan Prima Unggul yang menaungi para siswa SMA paket C mempunyai beberapa kegiatan usaha kecil yang memerlukan pencatatan akuntansi. Selama ini siswa mencatat keuangannya secara sederhana dan ringkas dan kadang kekurangan dana operasional. Kegiatan PKM ini dilaksanakan secara daring dengan pemaparan materi dan diskusi implementasinya sehingga siswa menjadi lebih memahami untuk Menyusun laporan keuangan dan membuat analisis rasio keuangan yang akan menggambarkan kondisi usaha bisnis mereka.